A4_6 Patrick's Plan - Wing, Matthew; Paton, Charlotte; Thomas, Kaia; McCabe, Nat (Physics Special Topics, 2021)
Within this paper we aim to investigate the feasibility of Patrick Star's suggestion to save a submerged city by simply pushing it somewhere else. This was done by investigating the frictional force that needs to be overcome if London was located on sand. It was concluded that a frictional force of 4.732*10^{13} N is required to move the city. Assuming an average human can push with roughly 123N this plan would take 5 times the population of Earth and hence would not be feasible.